Pelatihan Dan Pengenalan Dasar Microsoft Word Dalam Penggunaan Table of Content Dalam Menyusun Daftar Isi Tugas Dan Laporan Pada Yayasan Sosial Budaya Sosrokartono - Sejati Waluyo; Ferdiansyah; Ika Susanti (CV. Multi Kreasi Media, 2024)
In the current digital era, the use of computers as a medium for learning and working has become something that can no longer be avoided. The assignments given to students are also in digital form, whether the results are printed on a printer or in PDF format. So mastery of Microsoft Office has become a necessity. One of the school assignments that school children often receive today is to make written reports in various formats for class learning purposes. One of the difficulties faced by students is how to create a table of contents that can adapt to changing report pages. In this community service, the author conducted training in introducing Microsoft Word, especially the table of contents, to make the table of contents of reports and tasks easier.